Long‐Term Outcomes of Cardiac Sarcoid: Prognostic Implications of Isolated Cardiac Involvement and Impact of Diagnostic Delays - Joshua Sink; Cara Joyce; Max J. Liebo; David J. Wilber (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease, 2023)
Background Isolated cardiac sarcoid (iCS) is reported to have more severe clinical presentation and greater risk of adverse events compared with cardiac sarcoid (CS) with extracardiac involvement (nonisolated CS). Delays in diagnosing specific organ involvement may play a role in these described differences. Methods and Results A retrospective observational study of patients with CS over a 20‐year period was conducted. Objective evidence of organ involvement and time of onset based on consensus criteria were identified. CS was confirmed by histology in all patients from myocardium only (iCS) or extracardiac tissue (nonisolated CS). The primary end point was a composite of mortality, orthotopic heart transplant, and durable left ventricular assist device implantation. CS was isolated in 9 of 50 patients (18%). Among baseline characteristics, iCS and nonisolated CS differed significantly only in the frequency of sustained ventricular tachycardia at presentation (78% versus 37%; P=0.03) and delay in CS diagnosis >6 months (67% versus 5%; P<0.01). A nonsignificant trend toward lower left ventricular ejection fraction and more frequent heart failure in iCS was observed. Over a median follow‐up of 9.7 years (95% CI, 6.8–10.8), 18 patients reached the primary end point (13 deaths, 2 orthotopic heart transplants, and 3 durable left ventricular assist device implantations). The 1‐, 5‐, and 10‐year event‐free survival rates were 96% (95% CI, 85%–99%), 79% (95% CI, 64%–88%), and 58% (95% CI, 40%–73%), respectively, without differences between groups. There were no significant predictors of the primary end point, including delayed CS diagnosis. Conclusions Long‐term outcomes were similar between iCS and nonisolated CS in patients with histologically documented sarcoid. Diagnostic delays may contribute to differences in the dominant clinical presentation, despite similar outcomes.